From Sensory Experience to the Anthropology of Experience - Apostolova, Ivanka (Identities: Journal for Politics, Gender and Culture, 2011)
Author(s): Ivanka Apostolova Title (English): From Sensory Experience to the Anthropology of Experience Translated by (Macedonian to English): Stanimir Panayotov Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 139-146 Page Count: 8 Citation (English): Ivanka Apostolova, “From Sensory Experience to the Anthropology of Experience,” translated from the Macedonian by Stanimir Panayotov, Identities: Journal for Politics, Gender and Culture, Vol. 8, No. 1 (Winter 2011): 139-146.